Mice's Liver, Kidney, and Suprarenal Gland Histogenesis Mus Musculus - Sadiq, Dina H. (Universitas Muhammadiyah Sidoarjo, 2024)
This work used histological and histochemical methods to look at how the mice's liver, kidney, and suprarenal glands develop after birth. Therefore, using mice in scientific research is permissible. The experiment used thirty-two samples of the liver, kidney, and suprarenal gland of mice, eight at each age (one day, seven days, fourteen days, and twenty-one days). A thin capsule encased the liver on the first day of life; a thicker capsule encased it after 14 to 21 days. Hepatocytes made up the parenchyma, and a central vein encircled them. The parenchyma was further split by the sinusoids, and Next to the endothelial cells that encircled the hepatic sinusoids were protruding Kupffer cells. The liver measurements change with aging. Cortical, midcortical, and juxtamedullary renal corpuscles are distinguished by their increasing diameter with age. Distal convoluted tubules are shorter than the longest convoluted tubules, which are the proximal ones. Furthermore, Henle loops were short at one-day and adult ages but long at other ages. Highlights: Postnatal development of liver, kidney, and adrenal glands showed significant age-dependent structural changes in mice. Renal corpuscles increased in diameter with age, while Henle loops were short at 1 day and adulthood but elongated at intermediate stages. Histochemical analysis revealed well-developed basement membranes and tubular structures, indicating progressive organ maturation.